The "Studies in Ethnomethodology" Are a Way of Understanding and Handling Empirical Materials and Thoughts. Eric Laurier in Conversation With Hannes Krämer, Dominik Gerst & René Salomon - Laurier, Eric; Krämer, Hannes; Gerst, Dominik; Salomon, René (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In the following conversation Eric LAURIER talks about the role of ethnomethodology's foundational account—the "Studies in Ethnomethodology" (GARFINKEL, 1967)—within the UK and the influence of the book on his own research as well as on human geography, mobility studies, actor-network-theory, and a general social science methodology. He therefore underlines the peculiar focus of GARFINKEL on the everyday, his non-ironic position towards member's practices, and the plurivocality of the book. Giving an elaborated account on the methodological challenges with an ethnomethodological approach including video recordings he differentiates between the video as a research tool and video usage as a member's practice. LAURIER demonstrates the inspiring and initiating content of the studies as well as its limits. By doing so he can show the prolific quality for current research fields like the study of mobility and movement, the question of space and place, and the role of the "Studies in Ethnomethodology" as a political text.